(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Dengue has been a major health concern and currently there is no available option to treat the infection. It is an arboviral disease caused by dengue virus (DENV), an enveloped flavivirus. DENV initiates fusion process between viral envelope and host cell membrane, transfers its viral genome into target cell and infects host. Our research is focused on designing disulfide cyclic peptides that can fit into fusion cavity and interact with fusion peptide, interrupt conformational changes and therefore inhibit the fusion process. Computational approaches were conducted to calculate the binding affinity and stability of disulfide cyclic peptide ligands with target DENV E glycoprotein. Molecular docking and molecular dynamics simulation were performed using Molecular Operating Environment 2008.10 software (MOE 2008.10). Screening of 1320 designed ligands resulted in 3 best ligands, CLREC, CYREC and CYREC that can form interaction with target cavity and peptide fusion. These ligands showed good affinity with target DENV E glycoprotein based on free binding energy and interactions. To evaluate protein-ligand stability, we performed molecular dynamic simulation. Only CLREC showed protein-ligand stability and maintained interaction between ligand and target cavity. Therefore we propose CLREC as potential DENV fusion inhibitor candidates.Â Â